Preparing Unsocialized Youths for Additional Professions in Craft Fields (Zien Journal of Social Sciences and Humanities, 2022)
In this article, the content of entrepreneurial activities is shown in the orientation of school graduates, unorganized youth to national craft professions, non-organized youth, craft activities, the main directions of folk crafts, carpentry and entrepreneurial professions, cradle preparation and furniture production and sale